REALITAS SASTERA DAN REALITAS FIKSI DALAM KELUARGA PERMANA KARYA RAMADHAM KH - Sujarwanto, Sujarwanto (Jurnal Bestari, 1992)
The art and literarture reflected men behaviour and activities. The ain stream in cultural thought usually show us the great mirror of realities. It can be manifested in social and political aspect. In Indonesia, Ramadhan KH, was popular as one of the noted romantists and novelist . We agree with Culler's statement that the novel serves as the model by which society conceives as itself, the discourse in and through which it articulates the world. You can study one of his novels below summerized and analyzed by Sujarwanto.